Communication Strategies and Tactics as Key Points of Business Development - Machulska, Kateryna (Management and Administration Journal, 2019)
The study of communication strategies and tactics occupies an important niche in strategicmanagement. The relevance of this article lies in the fact that the interest of modern business administrationscience in the search for patterns and mechanisms of communication influence on the recipientis growing constantly. Communication strategies and tactics in the advertising of English-languageweb-recourses have been determined. We have defined two communication strategies for onlinestoresslogans: 1) a strategy of encouraging the consumer to choose the appropriate goods or service;2) a strategy of positioning the organisation in the market. Also various communication tactics,with the help of which those two strategies can be realised, have been described. They are: tactics ofappeal to the consumer; tactics of target group indication; tactics of ambiguity/disambiguity of theexpression, content and references; tactics of demonstration of the organisation's advantages anddisadvantages; tactics of emphasizing competence, experience, traditions and values; tactics ofgoods and services naming; tactics of using the store's name. In this article we try to identify which ofthem is the most effective. The proposed versions are based on the results of linguistic interviewing.